Analysis of Mining Crack Evolution in Deep Floor Rock Mass with Fault. (3rd December 2021) - Chen, Juntao; Zhang, Yi; Ma, Kai; Tang, Daozeng; Li, Hao; Zhang, Chengxiang
Abstract : To further explore the crack evolution of floor rock mass, the mechanism of fault activation, and water inrush, this paper analyzes the crack initiation and propagation mechanism of floor rock mass and obtains the initiation criteria of shear cracks, layered cracks, and vertical tension cracks. With the help of simulation software, the process of fault activation and crack evolution under different fault drop and dip angles was studied. The results show that the sequence of crack presented in the mining rock mass is vertical tension cracks, shear cracks, and layered cracks. The initiation and propagation of the shear cracks at the coal wall promote the fault activation, which tends to be easily caused at a specific inclination angle between 45° and 75°. The fault drop has no obvious impact on the evolution of floor rock cracks and will not induce fault activation. However, the increase of the drop will cause the roof to collapse, reducing the possibility of water inrush disaster. Research shows that measures such as adopting improved mining technology, reducing mining disturbance, increasing coal pillar size, and grouting before mining as reinforcement and artificial forced roof can effectively prevent water inrush disasters caused by deep mining due to fault activation.